Teaching for Transformation: Structured Cross-Cultural Experience in Transnational Contexts - Ming-yeh Lee; David Hemphill; Jacob Perea (Adult Education Research Conference, 2009)
The purpose of the study was to explore transformational learning in the context of cross-cultural, transnational study. In particular, it explored the ways in which a short-term study abroad program facilitated transformational learning opportunities for its adult participants. Data were collected through narrative surveys, students’ research projects, and researchers’ field notes to investigate promising program components and strategies.